Assessment of azole fungicides as a tool to control growth of Aspergillus flavus and aflatoxin B1 and B2 production in maize. Issue 6 (3rd June 2017) - Mateo, Eva M.; Gómez, José Vicente; Gimeno-Adelantado, José Vicente; Romera, David; Mateo-Castro, Rufino; Jiménez, Misericordia
ABSTRACT: Aspergillus flavus is a highly aflatoxin (AF)-producing species infecting maize and other crops. It is dominant in tropical regions, but it is also considered an emerging problem associated with climate change in Europe. The aim of this study was to assess the efficacy of azole fungicides (prochloraz, tebuconazole and a 2:1 (w/w) mixture of prochloraz plus tebuconazole) to control the growth of A. flavus and AF production in yeast-extract–sucrose (YES) agar and in maize kernels under different water activities ( a w ) and temperatures. Aflatoxins B1 and B2 were determined by LC with fluorescence detection and post-column derivatisation of AFB1 . In YES medium and maize grains inoculated with conidia of A. flavus, the growth rate (GR) of the fungus and AFB1 and AFB2 production were significantly influenced by temperature and treatment. In YES medium and maize kernels, optimal temperatures for GR and AF production were 37 and 25°C, respectively. In maize kernels, spore germination was not detected at the combination 37ºC/0.95 a w ; however, under these conditions germination was found in YES medium. All fungicides were more effective at 0.99 than 0.95 a w, and at 37 than 25ºC. Fungicides effectiveness was prochloraz > prochloraz plus tebuconazole (2:1) > tebuconazole. AFs were not detected in cultures containing the highest fungicide doses, and only very low AF levels were found in cultures containing 0.1 mg l – 1 prochloraz or 5.0 mg l – 1 tebuconazole. Azoles proved to be highly efficient in reducing A. flavus growth and AF production, although stimulation of AF production was found under particular conditions and low-dosage treatments. Maize kernels were a more favourable substrate for AF biosynthesis than YES medium. This paper is the first comparative study on the effects of different azole formulations against A. flavus and AF production in a semi-synthetic medium and in maize grain under different environmental conditions.